Teachers’ Multi-Experiences in Teaching Vocabulary for Students with Special Needs in Early Childhood Education - Nur Ayu Dwi Hartini (Universitas Islam Negeri Palopo, 2026)
This research examines the experiences of teachers in teaching vocabulary for students with special needs in early childhood education, focusing on the challenges faced and strategies used by teachers. This research was conducted in one of private schools that focuses on early childhood education in North Sumatra, Medan. Participants consisted of 2 teachers who have at least one year of experience in teaching early childhood students with special needs. A descriptive qualitative approach was adopted, utilizing Interpretive Phenomenological Analysis (IPA) to examine how teachers interpret and navigate their experiences. The findings revealed four main challenges: (a) language and communication barriers, (b) behavioral and emotional challenges, (c) lack of skills and experience, and (d) limited parental involvement. In terms of strategies, teachers employed (a) verbal methods, (b) gestural techniques, (c) visual aids, and (d) active parental involvement. These findings highlight the need for teacher training and stronger collaboration with parents to improve vocabulary acquisition for students with special needs.